Center-based patient care enhances survival of elderly patients suffering from peripheral arterial disease. (19th May 2017) - Höbaus, Clemens; Herz, Carsten Thilo; Obendorf, Florian; Howanietz, Marie-Therese; Wrba, Thomas; Koppensteiner, Renate; Schernthaner, Gerit-Holger
Abstract: Objectives: Recent advances in catheter-based intervention in patients with symptomatic peripheral arterial disease (PAD) have halved mortality. Mortality of PAD patients still remains high compared to other clinical forms of atherosclerosis. Intensified patient care might increase adherence to medical management and benefit the survival of PAD patients. Methods: Two patient cohorts were compared in a longitudinal prospective follow-up study. 370 PAD patients were included in the intensified center-based vascular medicine group (VMC group) and 332 PAD patients were treated by their usual primary care physician (PCP group). Survival in both groups was compared by Kaplan–Meier and Cox-regression analyses after 5 years. Results: Survival of patients in the VMC group was 90.8% compared to 66% in the PCP group. Thus, survival was improved by 24.9% by center-based care (absolute risk CI: 19–30.7%; 38% relative risk). PCP treatment increased all-cause mortality by a hazard ratio of 3.7 (95% CI: 2.5–5.5; p < .001). Mortality in the VMC group was significantly associated with the non-modifiable risk factors age, C-reactive protein, and nephropathy in multivariable analyses. Conclusion: These data imply that multi-morbid elderly PAD patients still benefit by intensified specialist care compared to the usual primary care setting. KEY MESSAGES: Center-based patient care improves survival in patients with peripheral arterial disease; mortality was reduced from 82 to 21 events per 1000 patient-years (rate ratio 0.26). Mortality was related to age (HR 1.46), CRP (HR 1.36), and nephropathy (HR 2.7). A multifactorial approach combining adequate drug prescription, accomplishment of agreed goals and repetitive training to initiate, implement, and persist treatment adaptations was applied.